In-situ synthesis of carbon-coated β-NiS nanocrystals for hydrogen evolution reaction in both acidic and alkaline solution. (16th August 2018) - Zhang, Jianfang; Wang, Yan; Cui, Jiewu; Wu, Jingjie; Shu, Xia; Yu, Cuiping; Bai, Huizhong; Zhai, Mengyuan; Qin, Yongqiang; Zheng, Hongmei; Zhu, Yanwu; Zhang, Yong; et al.
Abstract: The electrocatalytic hydrogen evolution reaction (HER) performance of carbon-coated β-NiS (NiS@C) nanocrystals has been investigated for the first time. The NiS@C nanocrystals were synthesized via a facile solvothermal method followed by in-situ carbonization process with the solvent (ethylene glycol) as the carbon source. Benefited from the well-dispersed NiS nanocrystals and the formation of carbon layer on NiS nanocrystals, the NiS@C nanocrystals displayed a high HER activity in 0.5 M H2 SO4, which needed an overpotential of 85 mV to achieve current density of 10 mA cm −1 with a Tafel slope of 46 mV dec −1, as well as long term stability for HER. Additionally, the NiS@C nanocrystals also showed efficient electrocatalytic activity under alkaline media. Highlights: NiS@C nanocrystals are prepared by solvothermal with in-situ carbonization method. Carbon layer increases the electric conductivity and durability of NiS nanocrystals. NiS@C nanocrystals exhibit enhanced HER activity under both acidic and alkaline media.